2021
DOI: 10.1155/2021/2087609
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between Different Degrees of Compression and Clinical Symptoms in Patients with Myocardial Bridge and the Risk Factors of Proximal Atherosclerosis

Abstract: Objective. To explore the relationship between different degrees of compression and clinical symptoms in patients with the myocardial bridge and the risk factors of proximal atherosclerosis. Methods. The clinical data of 156 patients with the myocardial bridge who underwent selective coronary angiography in our hospital from December 2010 to December 2015 were collected. The patients were divided into Noble grade I group (102 cases) and Noble grades II-III group (54 cases) according to the degree of mural coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
6
0
2
Order By: Relevance
“…The endothelial cell surfaces of the coronary artery in the proximal MB present rough worm-eaten-like defects. Platelets accumulate on the bare basement membrane, causing endothelial cells to detach from the basement membrane, leading to atherosclerotic plaques [22]. Therefore, there are several reasons to believe that the higher systolic compression of MB may have greater effects on the diastolic/systolic velocity ratio and would more easily lead to disturbances in blood flow and endothelial injury.…”
Section: Discussionmentioning
confidence: 99%
“…The endothelial cell surfaces of the coronary artery in the proximal MB present rough worm-eaten-like defects. Platelets accumulate on the bare basement membrane, causing endothelial cells to detach from the basement membrane, leading to atherosclerotic plaques [22]. Therefore, there are several reasons to believe that the higher systolic compression of MB may have greater effects on the diastolic/systolic velocity ratio and would more easily lead to disturbances in blood flow and endothelial injury.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of the MB is correlated with the risk of cardiovascular events such as atherosclerotic stenosis in the proximal part of the MB and may be affected by age, hypertension, Noble grade, and CRP level. 11 The middle portion of LAD (Mid-LAD) was predominantly the site for MB in most cases, 12 , 13 which can be diagnosed through angiography demonstrating the milking effect on the overlying bridged segment.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%